O documentário «Instituto Moderno do Porto»: quando imagens em movimento celebram a inovação pedagógica - Vieira, Helena Isabel Almeida (CEM – Cultura, Espaço & Memória, 2020)
Oporto’s Modern Institute was one of the most innovative educational institutions of the early 20th century in Portugal. Although it was opened only for a short period of time (1914‑1918), this school left us important sources so that its pioneering intention did not fall into oblivion. One of them is a documentary, of 1916, currently in the custody of the Portuguese Cinematheque. This set of moving images, crossed with other sources, iconographic and written, allow us to know the school spaces and its innovative educational practices, but also something rare in the study of the History of Education – see their teachers, their students and the educational activities that were developed there, making us go back in time and see a «living school».